Analysis of Health Promotion Methods for Adolescent Health Cadres in Bogor City: A Case Study - Siti Khodijah Parinduri; Andi Asnifatima; Dani Ferdian (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Health problems continue to increase, especially in non-communicable diseases, Basic Health Research (Riskesdas) 2018 shows that the stunting rate has decreased from 37.2 percent to 30.8 percent over five years, while malnutrition, from 19.6 percent to 17.6 percent shows a decline that is still not significant in a long period. On the other hand, the obesity rate actually increased from 14.8 percent to 21.8 percent and almost all non-communicable diseases had increased. This problem does not only occur at productive age or the elderly, in fact this problem can be the result of health problems during adolescence. In accordance with Permenkes Nomor 25 Tahun 2014 tentang Upaya Kesehatan Anak (Child Health Effort), it mandates the participation of youth in youth health services. This is to reduce health problems in adolescents and through adolescent approaches, one of which is through health promotion by youth health cadres. To analyze health promotion methods for youth health cadres based on school and community approaches as recommendations for health promotion methods for adolescents. The research method used is qualitative with a case study design (Creswell, 2014). The collection techniques used were online surveys, literature studies, in-depth interviews, FGDs, and desk studies. The data analysis technique used is Content Analysis. Then the results of the content analysis were continued by analyzing health promotion methods by academics and practitioners. Triangulation will be carried out by observation, interviews and focus group discussions. The results showed that health promotion methods were divided into two, namely methods for changing behavior and methods for influencing the environment. Health promotion methods for youth health cadres based on school and community approaches include education through social media, webinars, team building, competitions, discussions with practitioners, training, games, simulations, performances, and youth events. Health promotion methods for adolescent health cadres are dynamic in nature and continue to develop, so studies and research related to the effectiveness of health promotion need to be continuously developed.